A New Isocoumarin from Fermentation Products of Endophytic Fungus of Aspergillus versicolor - Ji, Bing-Kun; Dong, Wei; Wang, Yue-De; Zhou, Kun; Li, Yin-Ke; Zhou, Min; Du, Gang; Hu, Qiu-Fen; Ye, Yan-Qing; Yang, Hai-Ying (Asian Journal of Chemistry, 2015)
A new isocoumarin, versicoumarin D, was isolated from the fermentation products of an endophytic fungus Aspergillus versicolor. Its structure was elucidated by spectroscopic methods, including extensive 1D NMR and 2D NMR techniques. Compound 1 was also tested for its cytotoxicity against five human tumor cell lines (NB4, A549, SHSY5Y, PC3 and MCF7) and it showed high cytotoxicity against A549 and MCF7 cell with IC50 values of 5.8 and 8.0 μM, respectively.